Stress and antidepressants differentially regulate neurotrophin 3 mRNA expression in the locus coeruleus. - Smith, M A (1995)
The mechanisms by which stress and anti-depressants exert opposite effects on the course of clinical depression are not known. However, potential candidates might include neurotrophic factors that regulate the development, plasticity, and survival of neurons. To explore this hypothesis, we examined the effects of stress and antidepressants on neurotrophin expression in the locus coeruleus (LC), which modulates many of the behavioral and physiological responses to stress and has been implicated in mood disorders. Using in situ hybridization, we demonstrate that neurotrophin 3 (NT-3) is expressed in noradrenergic neurons of the LC. Recurrent, but not acute, immobilization stress increased NT-3 mRNA levels in the LC. In contrast, chronic treatment with antidepressants decreased NT-3 mRNA levels. The effect occurred in response to antidepressants that blocked norepinephrine uptake, whereas serotonin-specific reuptake inhibitors did not alter NT-3 levels. Electroconvulsive seizures also decreased NT-3 expression in the LC as well as the hippocampus. Ntrk3 (neurotrophic tyrosine kinase receptor type 3; formerly TrkC), the receptor for NT-3, is expressed in the LC, but its mRNA levels did not change with stress or antidepressant treatments. Because, NT-3 is known to be trophic for LC neurons, our results raise the possibility that some of the effects of stress and antidepressants on LC function and plasticity could be mediated through NT-3. Moreover, the coexpression of NT-3 and its receptor in the LC suggests the potential for autocrine mechanisms of action.